The alphabet house : [large type] a novel - Adler-Olsen, Jussi (Thorndike Press large print core, 2015)
British pilots James Teasdale and Bryan Young are chosen for a photo-reconnaissance mission looking for new Nazi factories that could turn the tide of the war. Shot down, James and Bryan know they will be executed if captured. They manage to jump aboard a train of wounded senior SS soldiers, throwing two patients off to take their places. But their act is too convincing: they end up in the Alphabet House, a mental hospital located far behind enemy lines.